2016
DOI: 10.1016/j.jcot.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-poor platelet-rich plasma to treat degenerative meniscal tear: A case report

Abstract: A traumatic and/or degenerative meniscus lesion is thought to be a clinical manifestation of early-onset osteoarthritis (OA), which is a chronic progressive condition that can cause substantial pain and disability. Platelet-rich plasma (PRP) is an emerging treatment option that has been reported to improve healing. Here, we present a case of a 29-year-old woman, with left anterior and medial knee pain, without history of trauma or injury. The patient was managed with leukocyte-poor PRP injections derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Moreover, a recent case report described the efficacy of PRP in a patient with a grade 3a medial meniscus tear. These patients were followed for 30 months after treatment and reported significant improvement in pain symptoms from baseline (VAS score = 70 mm; Global Rating of Change [GROC] score not available; KOOS score = 39) to 30 months (VAS score = 40 mm; GROC score = 5; and KOOS score = 63.1) . More recently, a double‐blinded randomized controlled trial was performed using PRP to augment direct meniscal repair of vertical longitudinal tears.…”
Section: Addressing the Treatment Gap—orthobiologicsmentioning
confidence: 99%
“…Moreover, a recent case report described the efficacy of PRP in a patient with a grade 3a medial meniscus tear. These patients were followed for 30 months after treatment and reported significant improvement in pain symptoms from baseline (VAS score = 70 mm; Global Rating of Change [GROC] score not available; KOOS score = 39) to 30 months (VAS score = 40 mm; GROC score = 5; and KOOS score = 63.1) . More recently, a double‐blinded randomized controlled trial was performed using PRP to augment direct meniscal repair of vertical longitudinal tears.…”
Section: Addressing the Treatment Gap—orthobiologicsmentioning
confidence: 99%
“…The literature search yielded 6 articles. [14][15][16][17][18][19] Most articles comprised active patients with a mean age of 28 to 29 years. The articles include case studies, 1 retrospective cohort study, and 1 longitudinal cohort study.…”
Section: Prp and Review Of Literaturementioning
confidence: 99%
“…20 The GROC score evaluates a patient's perception of improvement before the date of injury and after treatment, and the Tegner Activity Level Scale assesses knee function, including limping, support, instability, stair climbing, and squatting. 20 Betancourt et al 14 detailed a case study of a 29-year-old woman with a grade 3a medial meniscus tear confirmed on magnetic resonance imaging. She had pain with weight bearing, clicking, squatting, and changing positions from seated to standing and had previously tried hyaluronic acid injections.…”
Section: Prp and Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported on the use of PRP in meniscal injuries. Betancourt and Murrell reported on a case study with the use of a single PRP injection in a degenerative meniscus lesion with considerable improvement in pain symptoms [34].…”
Section: Introductionmentioning
confidence: 99%